The applicability of the metacognitive model of worry and generalized anxiety disorder in a non-clinical multi-ethnic sample of university students. (June 2015) - Pretorius, Chrisma; Walker, Stephen P; Esterhuyse, Karel G
This study explored the applicability of the metacognitive model of excessive worry and generalized anxiety disorder to the understanding of worry in a multi-ethnic context. A convenience sample of 1224 university students (female = 57.9%; Black = 49.9%) with a mean age of 19.77 years (standard deviation = 2.323) participated in the study. Following exploratory factor analysis, hierarchical regression analyses were employed to analyse the data. In combination, positive beliefs about worry, negative beliefs about worry, and cognitive control strategies emerged as significant predictors of worry intensity for the sample as a whole. However, only positive and negative beliefs about worry made independent contributions to the explanation of the variance in worry scores. Gender moderated the relationship between metacognition and worry. Viewing worry as a source of motivation was a unique predictor of worry intensity among women, while considering worry to be a positive personality trait emerged a distinctive predictor among males. The metacognitive model demonstrates cross-ethnic utility in understanding worry in a non-clinical population. The implications for theory and practice are discussed.